Effect of Magnetic Water on Some Physiological Aspects of Adult Male Rabbits: Khalisa Kadim Khudiar1 and Aous Muhammad Ali - Khudiar, Khalisa Kadim (The Iraqi Journal of Veterinary Medicine, 2012)
The present study was undertaken to search out thebeneficial effect of magnetized water on serumantioxidant, lipid profile and total protein of adult male rabbits. Twenty adult male rabbits were randomly divided into two equal groups and were treated daily for 60 days as follows:Group C:Rabbits of this group were allowed to ad libitumsupplyofdrinking water (control group),Group MG:Rabbits of this group were allowed to ad libitum supply of magnetic water.Fasting blood (for 8-12 hrs) samples were drawn by cardiac puncture technique at different times 0, 30 and 60 days of experiment for measuring the following parameters. Serum glutathione concentration (GSH), lipid profile including serum triacylglycerol (TAG), total cholesterol - (TC), high density lipoprotein - cholesterol (HDL-C), low density lipoprotein - cholesterol (LDL-C) and very low density lipoprotein cholesterol - (VLDL-C), total serum protein concentrations (TSP). The result revealed that drinking of magnetic water had beneficial effect on some physiological aspects manifested by a significant elevation in serum GSH, HDL-C and total serum proteins concentration. In addition to significant suppression in serums TC, TAG, LDL-C, and VLDL-C concentrations .In conclusion the results of this study pointed to the prevalence of magnetic water upon normal drinking water in all measures issued.